Pengaruh Love Of Money, Religiusitas, dan Time Budget Pressure terhadap Persepsi Etis Auditor - Kristi, Erin; Salim, Susanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Ethics is still a polemic in the world of auditors, especially with the increasing number of ethical cases involving auditors. Many factors can compromise an auditor's ethical perception. This research was conducted to empirically test the influence of love of money and religiosity on auditors, as well as time budget pressure during audit assignments on auditors' ethical perceptions. This research took the population and a sample of 31 respondents in the form of auditors working at Public Accounting Firms in DKI Jakarta using the questionnaire method as the data collection method. In this research, the data analysis technique used is multiple linear regression analysis via SPSS. This research provides results that the love of money variable has a positive influence on auditors' ethical perceptions. These results explain that the higher the love of money an auditor has, the more it will influence the auditor's ethics. The religiosity variable in this study has a positive effect on auditors' ethical perceptions, where these results show that the higher the auditor's level of religiosity, the more ethical the auditor will behave in carrying out his work. The research results for the time budget pressure variable explain that time budget pressure has no influence on auditors' ethical perceptions. These results indicate that pressure on the time budget during an audit engagement does not affect the auditor's ethical behavior in his work. Even though auditors have a limited time budget, they can carry out their work in audit engagements in accordance with a professional code of ethics honestly and with integrity.